VP171 The Safety Of Barbed Sutures In Cosmetic Surgery. (12th January 2018) - Du, Liang; Huang, Jin; Liao, Ga; Zhang, Yonggang; Lin, Yifei
Abstract : INTRODUCTION: Knotless barbed sutures can eliminate knot tying when patients are undergoing cosmetic surgery (CS). Although benefits reported on clinical outcomes are obvious, many studies have failed to demonstrate the potential for barbed sutures to mitigate adverse events. Thus, this study aimed to determine the safety of knotless barbed suture in CS. METHODS: PubMed, EMBASE, Cochrane Register of Clinical Studies, and ClinicalTrials.gov were searched for randomized controlled trials (RCTs) and cohort studies comparing barbed sutures with conventional sutures in CS (until 30 June 2016). Quality assessment was conducted using Cochrane recommendations. Review Manager was applied to analyze the data, and we sequentially omitted each study to perform sensitivity analyses. RESULTS: A total of five RCTs (low to moderate risk of bias) and six cohort studies (low to moderate risk of bias), proved eligible (3, 481 patients). The CS included body contouring operations, breast reconstruction, lipoabdominoplasty, abdominoplasty and wound closure of cesarean delivery. Comparing to conventional sutures, pooling data showed that general adverse events of barbed sutures were not significantly different (Odds Ratio, OR = .6, 95 percent Confidence Interval, CI .24 to 1.52, P = .28), while the subgroup analysis showed that fewer adverse events occurred in cohort studies, though with high heterogeneity (I 2 = 87 percent). Specifically, no significant differences were shown between barbed and traditional sutures in wound dehiscence (OR = .55, 95 percent CI .29 to 1.03, P = .06), incisional infection (OR = .56, 95 percent CI .22 to 1.48, P = .25), seroma (OR = .87, 95 percent CI .42 to 1.79, P = .70) and hematoma (OR = 1.52, 95 percent CI .29 to 7.99, P = .62). CONCLUSIONS: No differences were found between knotless barbed sutures and conventional sutures generally, but the cohort studies suggested barbed sutures resulted in fewer adverse events with longer follow-up. Thus barbed sutures are considered a safe surgical technique in CS. More evidence with larger sample sizes and longer follow up are needed to confirm the advantages of this technique in the future.